Drop in Sales Leads to Financial Distress: Evidence from selected Public Sector Chemical Companies in Kerala, India - Sunil Kumar, K.K; Renjith Mohan, P (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
A drop in sale and financial distress can be serious indicators of deeper business issues. A drop in sale refers to a noticeable decline in the volume or value of a company’s revenue over a period of time. This will lead to shrinking profit margin, cash flow problems, mounting debt or missed loan payments, and declining creditworthiness and eventually they will fall on financial distress. Financial distress is a serious problem faced by PSU’s in Kerala. Financial distress is a situation where firm’s operating cash flows are not sufficient to satisfy current obligations and the firm is forced to take half cooked measures. Use of Multiple Logistic Regression for predicting financial distress is a breakthrough in the field of accounting. Logit analysis provides a probability of financial distress. The results of the study propounded that the significant predictor variables of financial distress in the case of manufacturing Public Sector Undertakings working under the Chemical sector in Kerala, India.